Analysis of Digital Marketing Strategy Based on SOSTAC Method - Patni, Ni Putu Sri Ratih Dia; Susila, Anak Agung Ngurah Hary; Trisna, I Nyoman Prayana (Universitas Bina Darma, 2024)
PT Kana Bali Nature is a retail company of beauty and body care products in Denpasar, Bali, which has problems with decreased brand awareness and cost overruns due to suboptimal digital marketing implementation. This research aims to analyze and implement a thorough and comprehensive digital marketing strategy using the SOSTAC method which is flexible and effective enough to be used. The SOSTAC method includes situation analysis, setting 5S objectives and SMART Goals, STP Strategy, 7P Marketing Mix Tactic, Action, and Control with KPI metrics. The results of the 3-month research show that the digital marketing strategy carried out at PT Kana Bali Nature is quite effective. The majority of KPI indicators in each aspect managed to achieve targets such as an increase in revenue of up to 55.6% even though several other indicators were still declining. Suggestions and recommendations are given to maximize the company's future strategy. Keywords: Digital Marketing, SOSTAC method, marketing strategy, retail company